A rare reaction to a common procedure - anaphylactoid reaction to PEG push pad found in breast tissue markers - Ayvaz, Faruk; Low, Nicholas; Taylor, Kathleen; Bennett, Ian; Lloyd, Thomas (International Surgery Journal, 2025)
Polyethylene glycol (PEG) is a synthetic polymer used in a multitude of medical and non-medical settings. Allergy to PEG is a rare but potentially life-threatening condition. We report a case of an anaphylactoid reaction to the PEG component of a breast tissue marker and its subsequent removal using a vacuum assisted biopsy device. We believe this is an important case to draw attention to the fact that PEG is an additive in multiple medications and devices and the product information must be carefully reviewed when planning to administer a medication or device in a patient with a known PEG allergy. This case also highlights the use of vacuum assisted excision as an appropriate non-surgical means of intervention in managing this unusual event.